2004
DOI: 10.1080/13607860410001725072
|View full text |Cite
|
Sign up to set email alerts
|

Life-long intellectual activities mediate the predictive effect of early education on cognitive impairment in centenarians: a retrospective study

Abstract: The purpose of this study was to examine the hypothesis of whether early education and/or maintaining intellectual activities over the life-course have the power to protect against cognitive impairment even in extremely old adults. Ninety centenarians from the population-based Heidelberg Centenarian Study were assessed with a modified version of the Mini Mental State Exam (MMSE). Data about education, occupational status, and life-long intellectual activities in four selected domains were obtained. Results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 40 publications
5
44
0
Order By: Relevance
“…In the past, research concerning this concept has essentially studied the relations between metamemory and memory performances (Cavanaugh and Poon, 1989). Nevertheless, recent studies have shown that negative metamemory can reduce engagement in cognitive and social activities (Valentijn et al, 2006), whose effects are thought to have a positive impact on cognitive ageing (Hultsch et al, 1999;Kramer and Willis, 2002;Kliegel et al, 2004). Moreover, negative perceptions of one's own memory could reduce well-being (Mol et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, research concerning this concept has essentially studied the relations between metamemory and memory performances (Cavanaugh and Poon, 1989). Nevertheless, recent studies have shown that negative metamemory can reduce engagement in cognitive and social activities (Valentijn et al, 2006), whose effects are thought to have a positive impact on cognitive ageing (Hultsch et al, 1999;Kramer and Willis, 2002;Kliegel et al, 2004). Moreover, negative perceptions of one's own memory could reduce well-being (Mol et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both a city-oriented vocation that requires enhanced daily thought processing and a home in a suburban or city atmosphere where more visual, auditory, and interpersonal stimulation exists had seemingly similar effects. Numerous studies have found strong trends suggesting education level as a predictor for the onset of cognitive impairment, and that participation in life-long intellectual activity can be an important factor in staving off such symptoms (Callahan et al, 1996;Kliegel, Zimprich, & Rott, 2004;Marcopulos, McLain, & Giuliano, 1997;White et al, 1994). Similarly, intellectual stimulation can be seen as a technique to attenuate the harsh effects of cognitive impairment when it acts as a characteristic symptom of neurologic disorders such as multiple sclerosis (Sumowski, Wylie, Chiaravalloti, & DeLuca, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional risk might possibly result in changes to one's cognitive reserve. Although the initial level of reserve may be determined by innate differences in resources at birth, or by differences in cognitive activity as the brain matures in childhood, processes in young adulthood, midlife, and late life may also act to increase or decrease one's reserve (Kliegel et al, 2004). Thus, the absolute level of reserve may change throughout life.…”
Section: Discussionmentioning
confidence: 99%